Perancangan dan Pembuatan Sistem Informasi Administrasi pada Toko Gypsum Mulia Jaya - Hartono, Andryanto; Rostianingsih, Silvia; Setiabudi, Djoni Haryadi (Jurnal Infra, 2015)
Toko Gypsum Mulia Jaya is a company engaged in the sale and installation of Gypsum profile, partition, aluminum and some building materials. Currently, the recording system stock in Toko Gypsum Mulia Jaya still manually so that the accuracy of the data is less relevant and seems slow. Moreover the recording for each transaction is still not done. Based on the background of the problems in Toko Gypsum Mulia Jaya. In this design an information system that can record the purchase of administration, record keeping stock, conversion of goods, sales, reports and reminders to address the needs of every record store in the business process in question. The process of develop an application using Visual Basic 2010, while for the database using Sql Server 2008. The results obtained from the manufacture of administrative information system applications, among others, the purchase of material goods can be recorded into the database. Program helps recording all trading transactions. The process of checking the stock becomes easier and faster. Helping calculation of profit / loss for the income and expenditure. Display application is good enough and easy to use.